Socioeconomic Determinants of Sarcopenia among the Elderly Population in Mandera County, Kenya - Hamdi, Mohamed Ibrahim; Masinde, Lily; Juma, Rose (International Journal of Professional Practice, 2026)
Sarcopenia, characterized by the progressive loss of skeletal muscle mass, strength, and function, is a significant public health concern among aging populations. Limited data exist in resource-constrained settings like Mandera County, Kenya. This study assessed socioeconomic determinants of sarcopenia among the elderly in Mandera County. The study employed a descriptive cross-sectional design targeting individuals aged 65 years. A sample size of 186 participants was determined using the Cochran (1953) formula, with a multistage sampling approach to ensure representation across sub-counties, wards, and villages. Data collection involved non-structured questionnaires and physical measurements including handgrip strength, calf circumference, gait speed, and MUAC. Findings revealed that 60.7% of participants had confirmed severe sarcopenia. Socioeconomic factors significantly influenced status; 86% of those without health insurance exhibited confirmed or severe sarcopenia, compared to 14% with insurance (p = 0.019). Education was a key determinant (p< 0.001): 38.0% of those with no formal education and 49.0% with primary education had confirmed or severe sarcopenia, compared to 9.9% with secondary and 4.4% with tertiary education. Marital status (p = 0.261), living arrangement (p = 0.184), source of income (p = 0.879), and profession type (p = 0.141) showed no significant correlation. In conclusion, socioeconomic disadvantages contribute to severe sarcopenia. The study underscores the need for enhanced healthcare access for the elderly. It is recommended that county governments integrate routine sarcopenia screening into healthcare programs alongside community-based nutrition and physical activity initiatives. Further research should explore additional biological and environmental factors in similar low-resource settings.